Does the Medical Staff Performance are Determined by Altruism Behavior, Intellectual Capital, and Work Motivation? : Apakah Kinerja Tenaga Medis Ditentukan oleh Altruism Behavior, Intellectual Capital, dan Motivasi Kerja? - Alfadli Santowijaya; Muhammad Fachruddin Arrozi Adhikara; Rian Adi Pamungkas (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2023)
Introduction: Performance is determined by intellectual capital, behavioral altruism, and motivations that is directed toward a determined behavior. In practice, it is difficult to describe the action aspect of performance without referring to the outcome aspect. While performance is important as one of the indicators for hospitals for organizational continuity in providing complete services. Objective: This study aims to be able to evaluate the factors that determine the employees’ performance to be able to meet the organizational goals. More specifically, to find out how Altruism and Intellectual Capital affect performance mediated by work motivation. Methods: This study was conducted using primary data, namely by distributing questionnaires to respondents. SPSS and AMOS are used as statistical tools in processing the research data. Results: The results of the study found that the behavior of altruism, Intellectual capital, and work motivation simultaneously affects healthcare performance; altruism behavior affects motivation and performance; intellectual capital has a significant positive effect on motivation and performance; performance is determined by motivation positively but insignificantly; And motivation does not have a mediator role for the influence of altruism and intellectual capital behavior on performance. Conclusion: The Managerial Implications that can be applied by the management of Karya Medika 1 Hospital are by strengthening factors that can increase the employees' performance